Kemampuan Proses Pemecahan Masalah Matematis Siswa melalui Model Pembelajaran Creative Problem Solving dan Resource Based Learning (Studi Eksperimen pada Siswa Kelas X SMK Krija Bhakti Utama Limbangan) - Yopi Ahmad Sopian; Ekasatya Aldila Afriansyah (Universitas Hamzanwadi, 2017)
One of the important aspects in learning mathematics is problem-solving process ability that can be applied in real life. The purpose of this study is to assess the result of differences in the ability of students' mathematical problem-solving process ability that get the Creative Problem Solving and Resource Based Learning model. This research method is a quasi-experimental study; a sample population was students of SMK Bhakti Utama Krija. The results of this study were (1) There were differences students' mathematical problem-solving process ability to get the Creative Problem Solving and Resource Based Learning model. (2) Increasing problem-solving process ability by Creative Problem Solving model was moderate. (3) Increasing problem-solving process ability by Resource Based Learning model was low.